Quantitative Bestimmung von Neurorezeptoren: Die SPECf-Bildgebung muss verbessert werden - Kauppinen, T.; Yang, J.; Kilpeläinen, H.; Kuikka, J. T. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: Existing methods to determine the binding potential in brain receptor and transporter studies with single-photon emission computed tomography (SPECT) show a marked dependence on the physical performance of the scanner and on the regions of interest (ROIs) drawn. We examined the influence of the physical performance on the binding potential. Method: The authors tested three gamma cameras (single-, dual- and triple-head) and two reconstruction techniques (conventional filtered back-projection and iterative reconstruction method) to determine the binding potential in brain receptor studies. Both human and organ-like phantom studies were performed. Results: The binding potential was completely dependent on the imaging resolution, on the reconstruction technique used and on the ROIs drawn. The results of the phantom study revealed that the striatum-to-cerebellum ratio was only 37% of the actual one for the single-head, 63% for the dual-head and 72% for the triple-head gamma camera. Conclusion: The multiple head gamma camera with fan-beam collimators and iterative reconstruction with the attenuation based scatter correction is an imaging system of choice which introduces clinically more relevant images and is able to distinguish smaller differences in radioactivity at early stage of disease. However, for quantitative purposes the improvement without the use of the recovery coefficient is not great enough to restore the binding potentials to those of the true ones.
Keywords: Quantitation; neuroreceptors; iterative reconstruction; SPECT imaging